Studi Kelayakan Interoperabilitas Berbasis Open Archive Initiative Protocol For Metadata Harvesting: Studi Kasus Pada Perpustakaan Institut Pertanian Bogor - Muhammad Fadhli (Jurnal Pustakawan Indonesia, 2014)
ABSTRACTInteroperability is the ability to own two or more information systems to work together, especially in terms of data and information exchange and use data and information to achieve the purpose of information. Interoperability can work well if all the components have to meet the standards that have been set. Therefore was on this research, the authors will conduct a feasibility study on the management of OAI  -  PMH protocol on IPB library by comparing the objective conditions of the OIA  –  PMH library IPB standard OAI-PMH protocol and added to the 10 indicators supporting the development of standards based information system interoperability protocol OAI -PMH using a suitable list or checklist. The data was collected using interviews with library staff and staff  DIDSI  IPB and observation method to document associated with digital libraries and the OAI -PMH protocol, the library site and OAI - PMH protocol sites IPB Library. The results of this research may be one consideration in developing a library information system interoperability eventual goal is to improve the quality of information services to users.Keywords : feasibility studies , interoperability , OAI-PMH , digital libraries